Reproductive characteristics and kid marketing weights of hair goat flocks in rural conditions in Turkey - Atay, Okan; G?kdal, ?; Eren, V. (Cuban Journal of Agricultural Science, 2010)
This study has been carried out to determine vitality of kids and some reproductive characteristics according to kidding and growth of hair goats in rural farm conditions in Turkey. The reproductive performances related to two kidding seasons of the flocks in Kavsit village, ?ine, Ayd?n, in South-West Anatolia were recorded. A total of 840 goats and 772 kids in 6 rural farms were used in this study. The kidding results, fecundity, litter size, infertility rate and twinning rate were found to be 0.95, 1.09, 13.4 % and 9.21% , respectively. The age of the dam and the farm were significant sources of variation for the fecundity and the infertility rate of the animals.The vitality rates (%) of the kids until 7, 30, 60, 90 and weanning/marketing age were found as 94.11, 85.81, 81.82, 80.65 and 79.90 for two years. The number of weaned or marketed kids per served goat and per kidded goat were found as 0.78 and 0.90, respectively. The age of the dam and the farm were significant sources of variation for the number of weaned or marketed kids per served goat. The farm was only found to be a significant variable for the number of weaned or marketed kids per kidded goat. The liveweights of the marketed kids were found to be 26.65 kg. The results of this study have shown significant problems related to fertility and vitality in hair goat flocks in rural conditions. Key words: hair goat, reproductive charachteristics, vitality, rural conditions.